Proceedings of the Ninth International Conference on Entrepreneurship and Business Management (ICEBM 2020) 2021
DOI: 10.2991/aebmr.k.210507.019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brand Image, Website Quality, and Trust Towards Customer Loyalty in the Indonesian Consumer-to-Consumer (C2C) E-Commerce Business

Abstract: This study was commenced to understand the effect of brand image, website quality, and trust on loyalty in the Consumer-to-Consumer (C2C) E-Commerce business in Indonesia. This study used a survey method with the questionnaire as an instrument to gather the data required. As many as 350 respondents participated in this study, whereas all data was collected from those living in Jakarta. A total of 350 questionnaires were equally and virtually distributed to each respondent, in which, after further examinations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The hypothesis test results of this study contradict the conclusions who found that the quality of the website had a substantial impact on customer loyalty (Widayat, 2019;Wilson et al, 2019). This study confirms the findings of multiple prior studies that website quality has little effect on consumer loyalty (Avania & Widodo, 2022;Wilson, 2021). In order for the quality of the website to affect customer loyalty, it must be created in such a way that its use makes consumers feel satisfied, which in turn encourages consumer loyalty; if the consumer is not satisfied, however, the quality of the website has no effect on consumer loyalty.…”
Section: The Effect Website Quality On Customer Loyalty and Brand Lovesupporting
confidence: 62%
See 1 more Smart Citation
“…The hypothesis test results of this study contradict the conclusions who found that the quality of the website had a substantial impact on customer loyalty (Widayat, 2019;Wilson et al, 2019). This study confirms the findings of multiple prior studies that website quality has little effect on consumer loyalty (Avania & Widodo, 2022;Wilson, 2021). In order for the quality of the website to affect customer loyalty, it must be created in such a way that its use makes consumers feel satisfied, which in turn encourages consumer loyalty; if the consumer is not satisfied, however, the quality of the website has no effect on consumer loyalty.…”
Section: The Effect Website Quality On Customer Loyalty and Brand Lovesupporting
confidence: 62%
“…Online shopping is a solution where consumers can get the goods or services they want without having to go to a shopping center, but simply open a web or online shopping store application, look for the desired product or service and pay online through bank transfer facilities or online payment platforms. Consumer loyalty is influenced by the quality of a website (Widayat, 2019;Wilson, 2021). In several other studies, website quality does not have a significant effect on customer loyalty (Avania & Widodo, 2021;Kurniawan & Widodo, 2019;Wirapraja et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Similar results were found in Gonzalez et al (2015) research where he tried to find out of quality management tools in the evaluation of websites. Similar results were found in Wilson (2021) article, he chose for the study the type of C2C online store and researched product image, websites the impact of quality and trust on consumers' loyalty.…”
Section: Discussionmentioning
confidence: 62%